1961
DOI: 10.2514/8.5567
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurements and Theoretical Analysis of Detonation Induction Distances

Abstract: Experimental measurements of the induction distances are given for hydrogen-oxygen, acetyleneoxygen, acetylene-air, methane-oxygen, carbon monoxide-oxygen, hydrogen-oxygen-nitrogen, hydrogen-oxygen-helium, hydrogen-oxygen-argon, and hydrogen-oxygen-carbon dioxide mixtures at initial pressures of 1, 5, 10 and 25 atm. An empirical relationship involving the combustion temperature, burning velocity, sonic velocity in the unburned gas and Reynolds number based on the burning velocity has been established to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…We emphasize that the transition here occurs without acceleration of the reaction zone, which is often considered to play a key role in the DDT. It is interesting that, for wide tubes, the predetonation time and distance are effectively independent of the tube diameter, as is occasionally observed also in conventional DDT systems [20,21]. Further experimental/numerical evidence in support of the resistance concept comes from the transition in obstructed channels open at the ignition end [22,23].…”
Section: Overviewmentioning
confidence: 87%
“…We emphasize that the transition here occurs without acceleration of the reaction zone, which is often considered to play a key role in the DDT. It is interesting that, for wide tubes, the predetonation time and distance are effectively independent of the tube diameter, as is occasionally observed also in conventional DDT systems [20,21]. Further experimental/numerical evidence in support of the resistance concept comes from the transition in obstructed channels open at the ignition end [22,23].…”
Section: Overviewmentioning
confidence: 87%
“…Figure 5 shows the predicted DDT run-up lengths. The experimental results of Bollinger et al [8] were used for verification. Both the numerical model and the experimental results are sensitive to the initial composition of the mixture.…”
Section: Chemical Structure Of the Flamementioning
confidence: 99%
“…A review of the literature indicates there are several relevant studies including the experimental work of Bollinger et al [8] and Hinkey et al [9], two-dimensional numerical simulations by Kailasanath et al [10], onedimensional modeling by Brüls et al [11] and Smirnov and Panfilov [12], and the comprehensive overview of the gas-phase detonation theory presented by Oppenheim et al [13]. An interesting study of the DDT behavior as a function of the activation energy and the initial gas temperature was reported by Smirnov and Panfilov [12] who studied two distinct types of DDT initiation mechanisms: initiation of detonation from the flame zone and initiation along a contact discontinuity near the primary shock wave.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The run-up distance was found to be a minimum for stoichiometric mixtures. The effect of initial mixture temperature on the run-up distance was first studied by Lafitte (1928) and later by Bollinger et al (1961). In both these studies, it was shown that the run-2.…”
Section: Ddt Phenomena -A Brief Overviewmentioning
confidence: 99%